Pragmatics Analysis on Illocutionary Acts in Black Adam Movie - Lutviana, Via; Hendar, Hendar (JALL (Journal of Applied Linguistics and Literacy), 2024)
This research aims to analyze and describe the types of illocutionary act and the most dominant. The method used in this research is qualitative and descriptive method. The data used were taken from Black Adam movie released in 2022. This is a research about pragmatics study. The theoretical basis used in identifying types of illocutionary act is Searle in Hariati (2020). The result of this study show that there are five types of illocutionary act, they are assertive, directive, commissive, expressive, and declarative. The result showed that out of 115 data that have been analyzed, the illocutionary acts types were obtained namely 41 data assertive act or 35%, 33 data directive act or 29%, 17 data commissive act or 15%, 16 data expressive act or 14%, and 8 data declarative act or 7%. The most illocutionary act that occur is assertive act.